Evaluation of the Anti-Aging Effects of a Probiotic Combination Isolated From Centenarians in a SAMP8 Mouse Model - Fang, Xin; Yue, Mengyun; Wei, Jing; Wang, Yun; Hong, Daojun; Wang, Bo; Zhou, Xiaoting; Chen, Tingtao (Frontiers in Immunology, 2021)
Population aging is a prominent global problem in today's society. However, there are currently no good methods to treat or prevent aging, so anti-aging research has crucial implications. In this research, we screened bacteria from centenarians, and finally selected four probiotics (Lactobacillus fermentum SX-0718, L. casei SX-1107, Bifidobacterium longum SX-1326, and B. animalis SX-0582) to form a probiotic combination. By using the senescence accelerated mouse prone 8 (SAMP8) model, the anti-aging effects of the probiotic combination were evaluated by using behavioural testing, neuroinflammation, intestinal inflammation, and intestinal microbiota. The results showed that probiotic combination improved the impaired spatial memory, motor dysfunction, and decreased exploratory behavior in aging mice. The probiotic combination inhibited Toll-like receptor 4 (TLR4)/nuclear factor kappa B (NFκB)-induced neuroinflammation and up-regulated the expression of Sirt 1 to protect hippocampal neurons. At the same time, the probiotic combination regulated the intestinal microbiota, reduced the relative abundance of Alistipes and Prevotella in SAMP8 mice, inhibited TLR4/NFκB-induced intestinal inflammation, and increased the expression of intestinal permeability related proteins zonula occludens-1 (ZO-1) and Occuldin. The anti-aging effects of the probiotic combination may be through the regulating intestinal microbiota and inhibiting TLR4/NFκB-induced inflammation. This research provides the basis and technical support for the future production and application of the probiotic combination.